IMPLEMENTASI ALGORITMA HILL CIPHER DAN DISCRETE COSINE TRANSFORM DALAM KEAMANAN PESAN E-MAIL - Wulan, Sri; Hasugian, Abdul Halim; Suhardi, Suhardi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Regarding the security of email messages is very important in the digital era. So much data is sent via email every day. To improve the security of email messages, effective solutions can be applied to the Hill Cipher and Discrete Cosine Transform (DCT) algorithms. Hill Cipher is a classic encryption method that uses matrices to transform text. The combination of matrix operations can be decrypted without knowing the correct encryption key. Discrete cyclosine transform is a transformation method used in compressive images. In this study, we propose a combination of Hill cipher and DCT to protect email messages. Email messages are encrypted using the Hill Cipher algorithm, and the result is converted to the frequency domain using DCT. The step of improving upload security combines two mathematically different encryption methods. In addition, changing the frequency domain of the message reduces the success of attacks on the ciphertext. The researchers evaluated the performance of this combination of algorithms in terms of email message security, efficiency, encryption, decryption, and its impact on communication overhead. The Hill Cipher algorithm on messages in the form of voucher codes, speed and efficiency in cryptographic categorization are relatively fast, and for the insertion process with DCT, the MSE value is 130169.10 and the PSNR is -3.014 on an 8x8 image and 130169.10. 15920 x MPS. The combination of Hill Cipher and DCT is expected to improve the security of email messages without having a significant impact on system performance. Keyword: E-mail; Hill Cipher; Algoritma; DCT; Data Security Abstrak: Mengenai keamanan pesan email sangat penting di era digitalisasi. Begitu banyak data yang dikirim melalui email setiap hari. Untuk meningkatkan keamanan pesan email, solusi efektif dapat diterapkan pada algoritma Hill Cipher dan Discrete Cosine Transform (DCT). Hill Cipher adalah metode enkripsi klasik yang menggunakan matriks untuk mengubah teks. Kombinasi operasi matriks dapat didekripsi tanpa mengetahui kunci enkripsi yang benar. Transformasi siklosin diskrit adalah metode transformasi yang digunakan dalam gambar kompresif. Dalam studi ini, kami mengusulkan kombinasi kata sandi Hill dan DCT untuk melindungi pesan email. Pesan email dienkripsi menggunakan algoritma Hill Cipher, dan hasilnya diubah ke domain frekuensi menggunakan DCT. Langkah meningkatkan keamanan pengunggahan menggabungkan dua metode enkripsi yang secara matematis berbeda. Selain itu, mengubah domain frekuensi pesan mengurangi keberhasilan serangan terhadap ciphertext. Para peneliti mengevaluasi kinerja kombinasi algoritma ini dalam hal keamanan pesan email, efisiensi, enkripsi, dekripsi, dan dampaknya terhadap overhead komunikasi. Algoritma Hill Cipher pada pesan berupa kode voucher kecepatan dan efisiensi dalam kategorisasi kriptografi tergolong cepat, dan untuk proses penyisipan dengan DCT diperoleh nilai MSE sebesar 130169.10 dan PSNR sebesar -3.014 pada citra berukuran 8x8 dan 130169.10. 15920 x MPS. Kombinasi Hill Cipher dan DCT diharapkan dapat meningkatkan keamanan pesan email tanpa berdampak signifikan pada kinerja sistem. Kata kunci: E-mail; Hill Cipher; Algoritma; DCT; Keamanan Data